Peroxidase-like MoS2/Ag nanosheets with synergistically enhanced NIR-responsive antibacterial activities - Chen, Huiying; Zhao, Xinshuo; Cui, Bingbing; Cui, Haohao; Zhao, Mengyang; Shi, Jun; Li, Jingguo; Zhou, Zhan (Frontiers in Chemistry, 2023)
Pathogenic microbial infections have been threatening public health all over the world, which makes it highly desirable to develop an antibiotics-free material for bacterial infection. In this paper, molybdenum disulfide (MoS2) nanosheets loaded with silver nanoparticles (Ag NPs) were constructed to inactive bacteria rapidly and efficiently in a short period under a near infrared (NIR) laser (660 nm) in the presence of H2O2. The designed material presented favorable features of peroxidase-like ability and photodynamic property, which endowed it with fascinating antimicrobial capacity. Compared with free MoS2 nanosheets, the MoS2/Ag nanosheets (denoted as MoS2/Ag NSs) exhibited better antibacterial performance against Staphylococcus aureus by the generated reactive oxygen species (ROS) from both peroxidase-like catalysis and photodynamic, and the antibacterial efficiency of MoS2/Ag NSs could be further improved by increasing the amount of Ag. Results from cell culture tests proved that MoS2/Ag3 nanosheets had a negligible impact on cell growth. This work provided new insight into a promising method for eliminating bacteria without using antibiotics, and could serve as a candidate strategy for efficient disinfection to treat other bacterial infections.